« In partibus fidelium ». Missions du Levant et connaissance de l'Orient chrétien (XIXe-XXIe siècles) - Levant, Marie; Bourmaud, Philippe; Gabry-Thienpont, Séverine; Sanchez Summerer, Karène; Neveu, Norig (Collection de l'École française de Rome, 2022)
En quoi les missions chrétiennes du Levant ont-elles été des lieux de production de savoirs « orientaux » ? Comment ces connaissances ont-elles circulé de part et d'autre de la Méditerranée ? Comment ont-elles été reformulées et réappropriées localement ? Cet ouvrage se penche sur l'assimilation en Europe de connaissances relatives aux cultures chrétiennes-orientales et sur le rôle que les missions ont joué dans ce processus. Collectés et élaborés dans les grandes bibliothèques et universités européennes, puis intégrés par les structures de gouvernance des Églises, ces nouveaux savoirs ont aussi été réappropriés dans l'espace d'où ils étaient issus. Ils ont donné lieu à des prises de conscience patrimoniales à côté des expériences tragiques de la fin de l'Empire ottoman et de l'établissement de nouveaux États. Ce travail éclaire ainsi la dimension intellectuelle des dynamiques d'arabisation des Églises locales, de reformulation des frontières confessionnelles et de construction d'identités communautaires et nationales au Moyen-Orient. Il montre enfin comment les missions contribuent à la mise en valeur du patrimoine culturel oriental, et comment le domaine du savoir participe d'une évolution de la notion de mission depuis la période ottomane. In what ways were the Christian missions in the Levant places of production of 'oriental' knowledge? Many late nineteenth and early twentieth-century academics utilised knowledge production from Christian missions, notably by way of scholarly Orientalism. However, the history of this knowledge is also a history of representations: while missionary knowledge helped showcase the cultural and religious traditions of Eastern Christianity, what were the underlying motives and especially the consequences? This book examines the formulation and circulation of Eastern Christian knowledge on either side of the Mediterranean, the study of which is sometimes rooted in non-Anglophone academic traditions. The aim is to shed light on how knowledge relating to Eastern Christianity was assimilated in Europe, as well as the role missions played in this process, especially from the last third of the nineteenth century, when the institutions and instruments for the circulation of knowledge emerged. Another objective is to address the circulations and transformations of this knowledge on either side of the Mediterranean: collected and developed in major European libraries and universities, it was integrated by the governance structures of churches, but quite often also returned to the space it originated from, where it was reappropriated and gave rise to patrimonial processes, notably alongside the sometimes tragic experiences of certain communities during the end of the Ottoman Empire and the establishment of new states. Christian missions, at the intersection of East and West, were at the heart of this dynamic .